POLITICAL RELIGION: MARGINALIZATION OF LOCAL RELIGION IN INDONESIA - Sofwatul Ummah (Faculty of Ushuluddin UIN Syarif Hidayatullah Jakarta, 2022)
This article describes the chronology of recognition of formal religion and marginalization of local religion in Indonesia. Formally, the Indonesian government recognizes the formal religion based on the policy or the constitution in Indonesia. That is Presidental Decree number 1 the year 1965 and Constitution Number 5 the year 1969. According to the constitution, the formal religions are Islam, Christian, Catholic, Hinduism, Buddhism, and Confucianism. But Confucianism was marginalized on the new order of Indonesia based on the decree of the Ministry of Home Affairs year 1974. Because of this marginalization of Confucianism, the followers of it must fill the religion column with a stripe sign or choose five of formal religion. out from the five formal religion is considered as local religion or indigenous. But, in Indonesia, there is much local religion that has been existed centuries ago before the freedom of Indonesia. Even though based on The Ministry of culture and Tourism in 2003, there were 245 local religions in Indonesia. Because local religions were not recognized, it was thought that Indonesia had no religion before the first century. So, this article explains about 1) the chronology of recognition of formal religions and local/indigenous religion in Indonesia and 2) the effect of political religion on formal and local/indigenous religion. I argue that because of a narrow understanding of religion, so the policy or the constitution about religion in Indonesia seems narrow and impact on marginalization to civil society that believes in local religion/indigenous religion, because of this policy indigenous community in Indonesia do not have their rights such as recognition of the name of their indigenous religion in ID card and administration service. Then, this article is a descriptive with qualitative as an approach, and library research is used as the technique of collecting data.